Evaluation of Career Counseling Management on Career Maturity: A Cipp Model-Based Correlational Study - Ummi Qudsiyah; Akhmad Dasuki (Suluh: Jurnal Bimbingan dan Konseling, 2025)
This study evaluates career counseling management in three senior high schools in Palangka Raya City, Indonesia, using the CIPP model. Through a mixed methods approach, the study involved 186 grade XII students as well as in-depth interviews with counseling guidance teachers and school principals. The results showed that all CIPP dimensions were positively but weakly correlated with students' career maturity, with the Product dimension having the strongest relationship (r = 0.254). Multiple regression analysis showed a significant but limited influence of the CIPP dimensions on career maturity (R² = 0.109), with Product being the dominant predictor. Thematic analysis identified challenges with structural support, limited resources, and variable student engagement, indicating a gap between policy and practice. Overall, career counseling management is structured but not yet optimal in enhancing students' career maturity, requiring policy strengthening, resource development, and more personalized counseling strategies.